Apolipoprotein E mimetic peptide COG1410 combats pandrug-resistant Acinetobacter baumannii - Wang, Bo; Zhang, Feng-Wan; Wang, Wei-Xiao; Zhao, Yan-Yan; Sun, Su-Yue; Yu, Jin-Hong; Vitek, Michael P.; Li, George F.; Ma, Rui; Wang, Shiwei; Hu, Zhiliang; Chen, Wei (Frontiers in Microbiology, 2022)
The emergence of pandrug-resistant bacteria breaks through the last line of defense and raises fear among people of incurable infections. In the post-antibiotic era, the pharmaceutical field turns to seek non-conventional anti-infective agents. Antimicrobial peptides are considered a prospective solution to the crisis of antimicrobial resistance. In this study, we evaluated the antimicrobial efficiency of an ApoE mimetic peptide, COG1410, which has been confirmed to exhibit strong neural protective activity and immunomodulatory function. COG1410 showed potent antimicrobial activity against pandrug-resistant Acinetobacter baumannii, even eliminating large inocula (108 CFU/ml) within 30 min. LC99.9 in PBS and 50% pooled human plasma was 2 μg/ml (1.4 μM) and 8 μg/ml (5.6 μM), respectively. Moreover, COG1410 exhibited biofilm inhibition and eradication activity, excellent stability in human plasma, and a low propensity to induce resistance. Although COG1410 easily entered bacterial cytoplasm and bound to DNA nonspecifically, the major mechanism of COG1410 killing was to disrupt the integrity of cell membrane and lead to leakage of cytoplasmic contents, without causing obvious pores on the cell surface or cell lysis. Additionally, transcriptome analysis showed that treatment with COG1410-enriched genes involved a series of oxidation–reduction processes. DCFH-DA probe detected an increased ROS level in the presence of COG1410, indicating ROS was another hit of this AMP. Furthermore, the action of COG1410 did not depend on the electronic interaction with the LPS layer, in contrast to polymyxin B. The strong synergistic interaction between COG1410 and polymyxin B dramatically reduced the working concentration of COG1410, expanding the safety window of the application. C. elegans infection model showed that combined therapy of COG1410 and polymyxin B was capable of significantly rescuing the infected nematodes. Taken together, our study demonstrates that COG1410 is a promising drug candidate in the battle against pandrug-resistant A. baumannii.